The tidal disruption event AT 2018hyz – I. Double-peaked emission lines and a flat Balmer decrement. Issue 3 (2nd September 2020) - Short, P; Nicholl, M; Lawrence, A; Gomez, S; Arcavi, I; Wevers, T; Leloudas, G; Schulze, S; Anderson, J P; Berger, E; Blanchard, P K; Burke, J; et al.
ABSTRACT: We present results from spectroscopic observations of AT 2018hyz, a transient discovered by the All-Sky Automated Survey for Supernova survey at an absolute magnitude of MV ∼ −20.2 mag, in the nucleus of a quiescent galaxy with strong Balmer absorption lines. AT 2018hyz shows a blue spectral continuum and broad emission lines, consistent with previous TDE candidates. High cadence follow-up spectra show broad Balmer lines and He i in early spectra, with He ii making an appearance after ∼70–100 d. The Balmer lines evolve from a smooth broad profile, through a boxy, asymmetric double-peaked phase consistent with accretion disc emission, and back to smooth at late times. The Balmer lines are unlike typical active galactic nucleus in that they show a flat Balmer decrement (H α /H β ∼ 1.5), suggesting the lines are collisionally excited rather than being produced via photoionization. The flat Balmer decrement together with the complex profiles suggests that the emission lines originate in a disc chromosphere, analogous to those seen in cataclysmic variables. The low optical depth of material due to a possible partial disruption may be what allows us to observe these double-peaked, collisionally excited lines. The late appearance of He ii may be due to an expanding photosphere or outflow, or late-time shocks in debris collisions.